Novel fusion peptides deliver exosomes to modify injectable thermo-sensitive hydrogels for bone regeneration. (January 2022) - Ma, Shiqing; Wu, Jinzhe; Hu, Han; Mu, Yuzhu; Zhang, Lei; Zhao, Yifan; Bian, Xiaowei; Jing, Wei; Wei, Pengfei; Zhao, Bo; Deng, Jiayin; Liu, Zihao
Abstract: Injectable thermo-sensitive hydrogels composed of small intestinal submucosa (SIS) with exosomes derived from bone marrow mesenchymal stem cells (BMSCs) are desired for bone regeneration. However, poor mechanical properties limit the clinical application of SIS hydrogels. Herein, the mechanical properties of SIS hydrogels incorporated with 3-(3, 4-dihydroxyphenyl) propionic acid (CA) are assessed. The results show that the mechanical properties of SIS hydrogels are improved. In addition, the retention and stability of exosomes over time at the defect site are also challenges. Fusion peptides are designed by connecting collagen-binding domines (CBDs) of collagen type I/III with exosomal capture peptides CP05 (CRHSQMTVTSRL) directly or via rigid linkers (EAAAK). In vitro experiments demonstrate that fusion peptides are contribute to promoting the positive effect of exosomes on osteogenic differentiation of BMSCs. Meanwhile, the results of hydrogels combining exosomes and fusion peptides in the treatment of rat skull defect models reveal that fusion peptides could enhance the retention and stability of exosomes, thereby strengthen the therapeutic effect for skull defects. Therefore, SIS hydrogels with CA modified by fusion peptides and exosomes appear to be a promising strategy in bone regenerative medicine. Graphical abstract: Image 1